Developing Teaching Resources for Scientific Writing Based On Digital Comics - Anni Holila Pulungan (Asian TESOL Journal, 2023)
The teaching resources currently used by instructors are predominantly normative and verbally contextual. The language used is often challenging for students to comprehend, and these materials have not been integrated with modern technology like digital comics, especially in the scientific writing course. This study aims to investigate the suitability and effectiveness of digital comic-based teaching materials for scientific writing students in the English Education program. The research design for this study is Research and Development (R&D), utilizing the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Fourth-semester students in the English Education program serve as the data source for this study. Data collection is carried out through observations, interviews, questionnaire distribution, and conducting group discussion forums. Data are analyzed through needs analysis and objective analysis, as well as validation and reliability assessments. The overall results of these analyses are used as a basis for designing and developing digital comic-based teaching materials for the scientific writing course. Based on the analysis, it was found that the validation results for the digital comics of media expert validation was 3.75 which categorized into valid and content expert validation were 3.63 of learning aspects, meanwhile 3.71 of content aspect which fall into valid criteria. The results of students response was 4.33 which categorized into highly practical. This indicates that digital comic teaching materials are highly suitable for use in the scientific writing course.